Analyzing the Mediating Role of Organizational Commitment in the Relationship between Psychological Capital and Human Resource Productivity - FARD, MEHDI SADEGHI; SAYADI, SAEED; POURKIANI, MASOUD; SALAJEGHEH, SANJAR; BABAEI, HOJAT (The journal of contemporary issues in business and government, 2020)
The aim of this study is to identify the mediating role of organizational commitment in the relationship between psychological capital and human resource productivity. This study is an applied study in terms of aim and descriptive-correlational in terms of way of collecting data based on structural equation modeling. The statistical population of the present study is the employees of the affiliated departments of one of the governmental organizations of South Khorasan province, which included about 700 people in 2019. The sample size was 520 people and was selected using random sampling method. To collect the data, valid (Setiyanto & Natalia, 2017) Organizational Commitment Questionnaire and Luthans et al Psychological Capital Questionnaire were used, and a 31-item questionnaire was used to measure the variable of human resource productivity. In this questionnaire, the dimensions of ability, understanding and recognition, organizational support, motivation, feedback, credibility and adaptability were extracted from (Kumar & Agarwal, 2019) human resource productivity model and the dimension of effort was extracted from (Karakus et al., 2019) human resource productivity model. The Cronbach’s alpha coefficient was used to assess the reliability of the questionnaires, and the results indicated an acceptable value for the Cronbach’s alpha coefficient. The results of structural analysis of the research showed a positive and significant effect of psychological capital on human resource productivity (0.160) and also a positive and significant effect of psychological capital on organizational commitment (0.889). The results showed a positive and significant effect of organizational commitment on human resource productivity (0.847). Also, the research results indicate that psychological capital both directly and indirectly affects the productivity of human resources (0.753) through organizational commitment. Thus, the mediating effect of organizational commitment on the relationship between psychological capital and human resource productivity was confirmed.